Vibration Analysis of Circular Plates in Contact with Fluid: A Numerical Approach - Nair, Anju V.; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh (IOP Publishing, 2017)
A mathematical formulation to obtain the non-dimensionalized added virtual mass incremental factor for uniform circular plate in contact with fluid is presented. Based on Rayleigh's quotient, the natural frequencies can be evaluated using the added virtual mass incremental factors. A suitable approximation is used to describe the effect of non-dimensionalized added virtual mass incremental factors in the vibration analysis of circular plates. The numerical results obtained from the present formulation are compared with the known results reported in the literature and a good agreement was found. The maximum error percentage has been predicted from the present formulation is 0.005%.